Practice guideline update summary: Efficacy and tolerability of the new antiepileptic drugs II: Treatment-resistant epilepsy. Issue 4 (July 2018) - Kanner, Andres M.; Ashman, Eric; Gloss, David; Harden, Cynthia; Bourgeois, Blaise; Bautista, Jocelyn F.; Abou-Khalil, Bassel; Burakgazi-Dalkilic, Evren; Park, Esmeralda Llanas; Stern, John; Hirtz, Deborah; Nespeca, Mark; et al.
Objective: To update the 2004 American Academy of Neurology (AAN) guideline for managing treatment-resistant (TR) epilepsy with second- and third-generation antiepileptic drugs (AEDs).Methods: 2004 criteria were used to systematically review literature (January 2003 to November 2015), classify pertinent studies according to the therapeutic rating scheme, and link recommendations to evidence strength.Results: Forty-two articles were included.Recommendations: The following are established as effective to reduce seizure frequency (Level A): immediate-release pregabalin and perampanel for TR adult focal epilepsy (TRAFE); vigabatrin for TRAFE (not first-line treatment; rufinamide for Lennox–Gastuat syndrome (LGS) (add-on therapy). The following should be considered to decrease seizure frequency (Level B): lacosamide, eslicarbazepine, and extended-release topiramate for TRAFE (ezogabine production discontinued); immediate- and extended-release lamotrigine for generalized epilepsy with TR generalized tonic–clonic (GTC) seizures in adults; levetiracetam (add-on therapy) for TR childhood focal epilepsy (TRCFE) (1 month to 16 years), TR GTC seizures, and TR juvenile myoclonic epilepsy; clobazam for LGS (add-on therapy); zonisamide for TRCFE (6–17 years); oxcarbazepine for TRCFE (1 month to 4 years). The text presents Level C recommendations. AED selection depends on seizure/syndrome type, patient age, concomitant medications, and AED tolerability, safety, and efficacy. This evidence-based assessment informs AED prescription guidelines for TR epilepsy and indicates seizure types and syndromes needing more evidence. A recent FDA strategy allows extrapolation of efficacy across populations; therefore, for focal epilepsy, eslicarbazepine and lacosamide (oral only for pediatric use) as add-on or monotherapy in persons ≥4 years of age and perampanel as monotherapy received FDA approval.